Actions carried out in primary health care towards people with mental disorders: an integrative review - Priscilla Ingrid Gomes Miranda; Jackeline Vieira Amaral; Jaqueline Carvalho e Silva Sales; Fernando José Guedes da Silva Júnior; Ana Paula Cardoso Costa (Rev Rene)
Objective: to synthesize the types of actions developed by the multiprofessional team in the primary health care to people with mental disorders. Methods: integrative review, carried out in the databases Medical Literature Analysis and Retrieval System Online, via PubMed, Web Of Science, Literatura Latino-Americana e do Caribe em Ciências da Saúde, Base de Dados de Enfermagem, and Índice Bibliográfico Espanhol de Ciências de Saúde. Results: six studies were selected and grouped into the following axes: actions with the use of digital technologies (PyDeSalud.com platform; Partnering to Achieve School Success; Audio computer-assisted self-interview version of the Alcohol, Smoking and Substance Involvement Screening Test) and traditional actions (questionnaires during consultation; intervention in stages; support network to stop smoking). Conclusion: evidences show that traditional or digital actions in mental health are necessary to offer an integral care. The multiprofessional team has the tendency to incorporate digital technologies to care for these people.